Pengaruh Latihan Naik Turun Bangku Terhadap Hasil Lompat Jauh Gaya Jongkok Siswa Ektrakulikuler SMP Negeri 1 Sungai Pinang - Kurnia, Belinda; Destriani, Destriani; Yusfi, Herri (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This study aims to determine how much influence bench up and down training has on improving long jump results. The population in this study were students of SMP Negeri 1 Sungai Pinang who participated in athletics extracurricular activities in the long jump event with a sample of 32 students. This study was conducted using the one group pretest and posttest Experiment method. The instrument used in this study was to measure long jump results. The experimental treatment was in the form of bench up and down training carried out for six weeks or eighteen meetings with a training frequency of three times a week. The results of the study obtained the highest pretest value of 2.48m and the smallest value was obtained at 1.40m with an average value of 1.78, while the highest value in the posttest was obtained at 2.66 and the lowest value was 1.58 with an average value of 1.93, with t-test statistics with a significant level of α = 0.05, t count was obtained 11.432> t table 1.1697, so there is an influence on bench up and down training on the results of the squat style long jump. If t count> t table then Ho is rejected and Ha is accepted. Conclusion, in this study are that bench up and down training has an effect on increasing the results of the squat style long jump. Keywords: Training, bench up and down, long jump.